SPILLED GALLSTONES AT LAPAROSCOPIC CHOLECYSTSECTOMY – A REASON FOR RE-OPERATION IN THOSE WITH INCIDENTAL GALLBLADDER CANCER?. (8th June 2013) - Mayne, A I W; Ahmad, J; Jones, C; Dasari, B V; McKie, L D; Diamond, T; Loughrey, M; Taylor, M A
Abstract : Introduction: Laparoscopic Cholecystectomy is the gold standard treatment of symptomatic gallstone disease. Incidental gallbladder cancer is found in 0.6–2.1% of cases. Patients with Tis or T1a tumours generally undergo no further intervention. We present a case report and suggest the need for an aggressive management approach in patients with incidental Tis or T1a gallbladder cancer who had spilled stones at primary laparoscopic cholecystectomy. Method: A 37 year-old lady underwent a laparoscopic cholecystectomy for symptomatic gallstone disease. At operation, a number of gallstones were spilled into the peritoneal cavity. Subsequent histological examination showed an incidental pT1a gallbladder cancer, with areas of high grade dysplasia. HPB MDM discussion agreed on regular six-monthly outpatient follow-up. The patient re-presented to outpatient clinic 2 years later with recurrent right upper quadrant pain. Computed Tomography imaging revealed a small lesion in segment 6 of the liver. The patient underwent a diagnostic laparotomy which found multiple metastatic deposits, which on histological examination, were felt to have derived from the spilled gallstones at initial laparoscopic cholecystectomy. Due to the multiple metastatic deposits, the disease was un-resectable and she is to be treated with palliative chemotherapy. Results: Spilled gallstones occur in around 5-7% of laparoscopic cholecystectomies. There is a paucity of literature on the management of patients with spilled gallstones who subsequently are found to have incidental gallbladder cancer. Gallbladder cancers stage Tis or T1a have a favourable prognosis and are normally treated with simple cholecystectomy alone but this case has demonstrated a devastating outcome to this management approach. Conclusion: We suggest an aggressive management approach to patients with spilled gallstones who are subsequently found to have low grade Gallbladder Cancer.